Ouvir o falante eletrolaríngeo: comunicação oral, expressividade e efeitos de sentido - Vial, Tatiana Cavalcanti Lapa (2005)
Electrolaryngeal speech has specificities that may affect the communicative relationship between total laryngectomized patients and their interlocutors. The purpose of the present study was to get to know and to analyze the impressions and interpretations of listeners concerning electrolaryngeal speech with and without the image of laryngectomized patients during oral production, to assess the non-verbal expressive potential for production and transmission of sense effects. The method comprised two steps. The first step gathered 10 lay people and 14 speech and voice therapists to assess the speech of 4 electrolaryngeal speakers, without having their image. In the second step, subjects assessed the speech presented in the previous step but seeing the image of laryngectomized patients producing it. Results showed that in the first step, both lay people and speech and voice therapists were attained to the verbal content of the message, especially the limitations of speech intelligibility imposed by the use of the electrolarynx. In the second step, it was quite evident that gestures, change in posture and body tone and facial expressions maximized subjects' communication, providing an impression on the listeners and conveying dimensions capable of facilitating the communication between electrolaryngeal speakers and their interlocutors. Thus, we concluded that speech and voice therapy with total laryngectomized patients should emphasize communication as an inter-subject process that comprises the whole body, approaching non-verbal and related elements to improve communication of alaryngeal speakers and contributing to their subjective restructuring